2015
DOI: 10.1103/physrevb.92.054202
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of structural and magnetic nanoscale phase separation in layered cobaltites

Abstract: We report on the structural, electronic, and magnetic phases of a previously unexplored region in the phase diagram of GdBaCo 2 O 5+δ (δ = 0.57 and 0.63). Despite a homogenous average structure displayed by both the samples, the orthorhombic highly oxygenated GdBaCo 2 O 5.63 shows clear signatures of structural nanoscale phase separation. By combining a pair distribution function with photoluminescence and electron spin resonance techniques, we found that the nanoscale phase separation is induced by an inhomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As the applied potential shifts from 0 to −0.3 V vs RHE, the A 1g peak of Co Oh for both Co 3 O 4 and MgCo 2 O 4 gradual ly becomes weaker and wider (Figure d,e), which may be attributed to the electrochemical reduction for generating O v on Co Oh sites. When the potential negatively shifts to −0.4 V vs RHE, a new subpeak can be observed on the A 1g peak, indicating the generation of a new Co Oh sites, which can be identified as Co Oh with local distorted coordination structure induced by the O v . Furthermore, with the potential further negatively shifting to −0.9 V vs RHE, the intensity of this subpeak is rapidly enhanced, further verifying that the new subpeak originates from the generation of O v resulted from the electrochemical reduction (Figure e). In sharp contrast, the F 2g 1 peak of Co Td for Co 3 O 4 remains almost unchanged during the whole potential shift process, reflecting the absence of an electrochemical change at Co Td during the NO 3 – RR.…”
Section: Resultsmentioning
confidence: 68%
“…As the applied potential shifts from 0 to −0.3 V vs RHE, the A 1g peak of Co Oh for both Co 3 O 4 and MgCo 2 O 4 gradual ly becomes weaker and wider (Figure d,e), which may be attributed to the electrochemical reduction for generating O v on Co Oh sites. When the potential negatively shifts to −0.4 V vs RHE, a new subpeak can be observed on the A 1g peak, indicating the generation of a new Co Oh sites, which can be identified as Co Oh with local distorted coordination structure induced by the O v . Furthermore, with the potential further negatively shifting to −0.9 V vs RHE, the intensity of this subpeak is rapidly enhanced, further verifying that the new subpeak originates from the generation of O v resulted from the electrochemical reduction (Figure e). In sharp contrast, the F 2g 1 peak of Co Td for Co 3 O 4 remains almost unchanged during the whole potential shift process, reflecting the absence of an electrochemical change at Co Td during the NO 3 – RR.…”
Section: Resultsmentioning
confidence: 68%
“…It has been observed that the oxygen vacancies in the lanthanide plane (RO δ ) of RBaCo 2 O 5.5+ δ are ordered for δ = 0 and δ = 0.25 while no vacancy ordering has be detected for δ = 0.37 and δ = 0.5. Moreover, with increasing δ value of RBaCo 2 O 5.5+ δ , metallic Co 4+ sites increase while oxygen vacancies on Co 3+ sites decrease in the lattice (detailed electronic structures and local coordination environments are provided in Figure a and Discussion 2 in the Supporting Information). Herein, motivated by the tunability and controllability of both the oxygen vacancies at pyramidal Co 3+ sites (Co 3+ pyr ) and the metallic Co 4+ ions at octahedral sites (Co 4+ oct ) in this family, we attempt to develop a superior cobalt‐based perovskite‐type oxide toward the alkaline HER.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with increasing δ value of RBaCo 2 O 5.5+ δ , metallic Co 4+ sites increase while oxygen vacancies on Co 3+ sites decrease in the lattice (detailed electronic structures and local coordination environments are provided in Figure a and Discussion 2 in the Supporting Information). Herein, motivated by the tunability and controllability of both the oxygen vacancies at pyramidal Co 3+ sites (Co 3+ pyr ) and the metallic Co 4+ ions at octahedral sites (Co 4+ oct ) in this family, we attempt to develop a superior cobalt‐based perovskite‐type oxide toward the alkaline HER. Theoretically, we predict a synergistic effect of two active sites on RBaCo 2 O 5.5+ δ surfaces from our computational studies, namely, the oxygen vacancies at Co 3+ pyr sites and O 2p ligand holes (OLH) of oxygen atoms from the Co 4+ oct clusters can be active sites for H 2 O adsorption and H 2 desorption, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To validate this hypothesis, we studied the evolution of the ESR signal as a function of doping at room temperature. ESR allows direct access to the spinenvironment interactions of Fe ions in different valence states [29], [30].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of a strong isotropic exchange interaction, like SE, the Gaussian ESR line, which depends on the magnetic dipole interaction ( H d ), is narrowed into a Lorentzian line by fast dynamics resulting from the exchange coupling ( J ) according to ΔH pp ≈ H d 2 /ω ex where ω ex ≈ J / ℏ , i.e., exchange narrowing . , Conversely, the DE heterospin dipolar interaction gives rise to an effective alternating FM internal magnetic field that relaxes the Fe 3+ spins . Upon doping, one could expect an increase of the spin relaxation rate of Fe 3+ that produces the broadening of the ESR signal, i.e., exchange broadening .…”
Section: Resultsmentioning
confidence: 99%